Circularly polarized antennas - Gao, Steven; Luo, Qi, 1982-; Zhu, Fuguo; IEEE Xplore (Online Service); Wiley (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2014)
This book presents a comprehensive insight into the design techniques for different types of CP antenna elements and arraysIn this book, the authors address a broad range of topics on circularly polarized (CP) antennas. Firstly, it introduces to the reader basic principles, design techniques and characteristics of various types of CP antennas, such as CP patch antennas, CP helix antennas, quadrifilar helix antennas (QHA), printed quadrifilar helix antennas (PQHA), spiral antenna, CP slot antennas, CP dielectric resonator antennas, loop antennas, crossed dipoles, monopoles and CP horns. Advanced designs such as small-size CP antennas, broadband, wideband and ultra-wideband CP antennas are also discussed, as well as multi-band CP antennas and dual CP antennas. The design and analysis of different types of CP array antennas such as broadband CP patch arrays, dual-band CP arrays, CP printed slot arrays, single-band and multi-band CP reflectarrays, high-gain CP waveguide slot antennas, CP dielectric resonator antenna arrays, CP active arrays, millimetre-waveband CP arrays in LTCC, and CP arrays with electronically beam-switching or beam-steering capabilities are described in detail. Case studies are provided to illustrate the design and implementation of CP antennas in practical scenarios such as dual-band Global Navigation Satellite Systems (GNSS) receivers, satellite communication mobile terminals at the S-band, Radio Frequency Identification (RFID) readers at 2.4 GHz, and Ka-band high-speed satellite communication applications. It also includes the detailed designs for a wideband Logarithmic spiral antenna that can operate from 3.4-7.7 GHz. In addition, the book offers a detailed review of the recent developments of different types of CP antennas and arrays. -- -- . Presents comprehensive discussions of design techniques for different types of CP antennas: small-size CP antennas, broadband CP antennas, multi-band CP antennas and CP arrays.. Covers a wide range of antenna technologies such as microstrip antennas, helix, quadrifilar helix antenna, printed quadrifilar helix antenna, dielectric resonator antennas, printed slots, spiral antennas, monopoles, waveguide slot arrays, reflectarrays, active arrays, millimetre-wave arrays in LTCC, electronically beam-switching arrays and electronically beam-steerable arrays.. Reviews recent developments in different types of CP antennas and arrays, reported by industries, researchers and academics worldwide.. Includes numerous case studies to demonstrate how to design and implement different CP antennas in practical scenarios.. Provides both an introduction for students in the field and an in-depth reference for antenna/RF engineers who work on the development of CP antennas.Circularly Polarized Antennas will be an invaluable guide for researchers in R&D organizations; system engineers (antenna, telecom, space and satellite); postgraduates studying the subjects of antenna and propagation, electromagnetics, RF/microwave/millimetre-wave systems, satellite communications and so on; technical managers and professionals in the areas of antennas and propagation.
6.5 CP Reflectarray for Ka Band Satellite Communications 284 -- 6.6 Circularly Polarized Logarithmic Spiral Antenna with a Wideband Balun 293 -- 6.7 Summary 301 -- References 303 -- Index 305.
In Wiley online library
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/22/2015.
Keywords: Spiral antennas; Transmitting antennas; Antenna radiation patterns; Polarized beams (Nuclear physics); Electronic books